A triple band modified F-shaped monopole antenna for RFID application - Spoorti Barigidad; Aishwarya C. Yeshawant; Sridevi Rao; Tharunya C. A.; Tanweer Ali; Sameena Pathan (Institute of Advanced Engineering and Science, 2020)
Radio frequency identification (RFID) is a very prominent technology and is used in object-attached identification and tracking tags. In this paper a triple band monopole antenna is designed to work at 2.2-2.6 GHz (lower RFID band), 5.3-6.8 GHz and 8.7-9.5 GHz (upper RFID band) frequency ranges. The antenna design resembles a modified F-shaped radiator and is built on a low cost easily available FR4 dielectric substrate. Initially an F-shaped radiator with partial ground plane is studied which exhibits the operation at 2.6 and 6.5 GHz. Further, modifying this F-shaped radiator exhibits an additional resonance at 9.2 GHz. Fundamental characteristics such as reflection coefficient (S11), radiation pattern and 3D gain have been analyzed and good results have been obtained. Parametric analysis is carried out to fix the optimized antenna dimensions. All the simulations are carried out using the high frequency structure simulator software (HFSS). The antenna structure is easy to design and produce, and ideal for use in RFID applications.document quickly and accurately, to determine its relevance to their interests, and thus to decide whether to read the document in its entirety.